Carbimazole-related agranulocytosis in pregnancy - A case report - Lim, S.S.; Shireene, V.; Vijay, A.; Tan, T.B.A.; Pendek, Rokiah; Chan, S.P. (Faculty of Medicine, University of Malaya, 2007)
We report a 33-year-old Malay lady who presented with fever, tonsillitis and pharyngitis a month after initiation of antithyroid therapy (carbimazole 15 mg tds) for thyrotoxicosis by her general practitioner. She was still clinically and biochemically thyrotoxic but not in thyroid storm. At that time, she was also confirmed to be four weeks pregnant. Her full blood count revealed neutropaenia with an absolute neutrophil count of 0.036 ' 109/L. Bone marrow aspirate and trephine were compatible with carbimazole-related agranulocytosis. Carbimazole was discontinued and she was given broad spectrum antibiotics and Granulocyte Colony Stimulating Factor (GCSF), to which she responded. Verapamil was used for symptomatic heart rate control instead of beta-blockers as she had a history of bronchial asthma. The patient subsequently opted for termination of pregnancy after which she was given radioactive iodine I131 (10 mCi) for definitive therapy of her thyrotoxicosis. In conclusion, carbimazole-related agranulocytosis is an important entity to recognise and treat early to prevent morbidity and mortality. Termination of pregnancy was carried out as the treatment given during the episode of agranulocytosis may have negative effects on foetal viability and growth.